Field detection of Tritrichomonas foetus through loop mediated isothermal amplification with CELDA - Oyhenart, Jorge (2022)
An affordable, portable, and easy-to-build instrument was implemented to perform loop-mediated isothermal amplification (LAMP) in the field. Controlled by Arduino, CELDA heats the reaction tubes, reads the intensity of green fluorescent light and stores data in a computer. In the laboratory and in the field, CELDA was successfully used for the detection of Tritrichomonas foetus DNA in less than 60 min and helped distinguish positives with less difficulty than visual inspection.